Reproduksi Budaya Pambiwara dalam Upacara Pernikahan Adat Jawa - Mahendra Wijaya; Sri Hilmi Pujihartati; Sudarsana Sudarsana; Marimin Marimin; Triana Rahmawati (Society, 2024)
This article explores the efforts of Sanggar Permadani in developing, preserving, and sustaining Javanese culture. The primary focus of the Javanese cultural heritage preserved by Sanggar Permadani is pambiwara, individuals responsible for organizing and guiding traditional Javanese ceremonial events. This preservation is crucial as fewer people are performing traditional Javanese wedding ceremonies and employing the services of pambiwara. This qualitative study employs an ethnographic approach, with data collected through observations, interviews, and documentation. The findings reveal that Sanggar Permadani has successfully preserved Javanese culture by training new generations of pambiwara through annual courses or training sessions held over five months. All participants are of Javanese descent and come from diverse educational backgrounds. To date, Sanggar Permadani has graduated 20 cohorts. The findings align with Pierre Bourdieu’s theory of cultural capital and embodied state, which posits that individuals shape their identity based on cultural capital and educational investment imparted from birth.